Aplicação de eliminação iterada de estratégias dominadas a modelos de competição entre dois jogadores - Oliveira, João Paulo Caraú de (2018)
In this dissertation we present the study and application of a tool derived from the Theory of Games called the iterated elimination of strictly dominated strategies or actions (IESD). Using the Python programming language, this work focuses on the construction and application of an algorithm based on this tool to solve a hypothetical situation of conflict between two spaceships. The analysis takes place from the perspective of one of the players and various models of distributions to qualify how a winner is chosen are adopted and simulated. To win one of the players must make a series of path choices to be a winner, and a wrong choice means their destruction. In general the use of IESD was more advantageous than the random choice.